Epidemiology of mental health comorbidity in psoriasis. (4th July 2018) - Wu, J. J.; Feldman, S. R.; Koo, J.; Marangell, L. B.
Abstract: Aim: The occurrence of mental health comorbidities such as depression, anxiety, and suicidal ideation or behavior is not uncommon in the context of psoriasis. The negative influence of psoriatic disease on a patient's physical and mental well-being, in combination with overlapping pathophysiology, increase the risk for clinically significant psychiatric conditions. These psychiatric conditions, in turn, influence the patient's outlook and potentially, prognosis. Although the healthcare community increasingly recognizes the association of mental health comorbidities with psoriasis, the extent of the correlation is not fully appreciated. To better understand the relationship between mental health comorbidities and psoriasis, including prevalence, risk factors, and response of psychiatric comorbidities to psoriasis treatment, a narrative review of the published literature was conducted. Methods: Data from epidemiologic, observational, and clinical studies demonstrate a substantially greater mental health comorbidity burden in patients with psoriasis compared with those without psoriasis or patients with other dermatologic conditions. Result: The influence of contemporary drug therapies on measures of depression and anxiety are predominantly positive, although further data are needed to better understand the effects of long-term therapy. Conclusion: Clinicians should consider the heightened potential for mental health comorbidities when determining an optimal management strategy for their patients with psoriasis.